Synthesis and oxygen reduction application of metal cluster / polyphthalocyanine network compounded organic electrocatalytic material

Through metal cluster/polyphthalocyanine network composite technology, the problem of existing ORR electrocatalysts relying on precious metals is solved, and efficient and low-cost catalytic effect is achieved, and the oxygen reduction reaction performance is improved at low overpotentials.

CN119771497APending Publication Date: 2025-04-08LANZHOU JIAOTONG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411658895.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing oxygen reduction reaction (ORR) electrocatalysts rely on precious metals, are costly and limited in resources, and the ORR performance of organic materials at low overpotentials leads to low energy conversion efficiency.

Method used

The organic electrocatalytic material was prepared by metal cluster/polyphthalocyanine network composite. The synergistic effect of the metal cluster and substituents was improved in the metal-organic framework to improve the catalytic activity of ORR.

Benefits of technology

It achieves an efficient catalytic effect similar to a platinum-based catalyst, significantly reduces the catalyst cost, enhances service life, and improves ORR performance at low overpotentials, overcoming the shortcomings of poor stability and low catalytic activity of traditional organic catalytic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005142775680000011
    Figure HDA0005142775680000011
  • Figure HDA0005142775680000012
    Figure HDA0005142775680000012
  • Figure HDA0005142775680000013
    Figure HDA0005142775680000013
Patent Text Reader

Abstract

The invention provides synthesis and oxygen reduction application of a metal cluster / polyphthalocyanine network compounded organic electrocatalytic material. The preparation method comprises the following steps: by taking benzene ring-containing anhydride, chlorate and urea as raw materials, carrying out high-temperature reaction, cooling, and purifying for multiple times, so as to obtain an edge-functionalized polyphthalocyanine network precursor; dispersing the obtained polyphthalocyanine network precursor into a solution A by using a proper solvent; meanwhile, trifluoroacetate and a tert-butyl metal compound are mixed in a proper solvent to form a metal cluster, and the metal cluster compound is dissolved in the solvent to form a solution B; and mixing the two solutions, standing overnight, filtering, purifying, and carrying out ball milling treatment to finally obtain the target metal cluster / polyphthalocyanine network composite organic catalyst. The polyphthalocyanine oxygen reduction organic catalytic material designed by the invention is low in raw material cost and simple to prepare. The test shows that the half-wave potential of the material is 100 mV higher than that of Pt / C, the E1 / 2 reduction value is 30 mV lower than that of Pt / C after accelerated aging for 2500 circles, and the material has high activity and high stability and can be applied to devices such as lithium batteries and fuel batteries related to the oxygen reduction process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery material preparation, and relates to a synthesis of an organic electrocatalytic material prepared by using a metal cluster / polyphthalocyanine network composite. The catalytic material is mainly used in oxygen reduction reactions, and mainly involves the negative electrode process of batteries such as lithium batteries, fuel cells, sodium batteries and zinc-air batteries. Background Art

[0002] The oxygen reduction reaction (ORR) is a key process occurring at the cathode in lithium batteries, fuel cells and zinc-air batteries, and its efficiency directly affects the overall performance of the battery. As a key reaction in energy conversion technology, ORR plays a vital role in high-energy, high-efficiency and environmentally friendly energy storage and conversion systems (such as metal-air batteries and fuel cells). However, the slow ORR is highly dependent on traditional reactive platinum group metal (PGM)-based electrocatalysts. Because the high price of precious metals and limited natural resources limit their large-scale application, researchers need to develop other PGM-free electrocatalyst candidate materials. Among them, tetrapyrrole (such as porphyrin and phthalocyanine) transition metals (Co, Fe, etc.) have been widely studied and classified as expected model systems due to their good catalytic performance.

[0003] In recent years, composite organic oxygen reduction electrocatalytic materials that benefit from electron delocalized conjugated systems and clear active sites to provide higher metal site density and conductivity have attracted much attention due to their excellent properties such as high activity, use of non-precious metals, good reactivity, environmental friendliness and low cost, controllability, and high specific surface area. However, organic materials have the defects of poor stability and low catalytic activity, especially ORR performance at low overpotential, which leads to low energy conversion efficiency.

[0004] The polyphthalocyanine used in the present invention is a macrocyclic metal structure containing in-plane π conjugation, which constitutes a metal phthalocyanine (M-Pc, M=Cu, Co, Zn, Cr, Ni, Fe and Mn) catalytic material with different metal centers. This type of polyphthalocyanine macrocyclic structure can not only be modified in a diversified manner by organic groups to provide abundant coordination sites, but also form polyphthalocyanine derivatives with different symmetries and sizes, which is helpful for catalytic optimization in oxygen reduction reaction (ORR); in addition, during the synthetic polymerization process, the acid anhydride acts as an edge blocking agent to prevent cross-linking reaction, thereby forming a structure with corresponding edge functionalization on the polyphthalocyanine network. In combination with the synergistic effect of the metal cluster, the conductivity and catalytic activity of the electrocatalytic material can be significantly enhanced. Finally, the present invention synergistically couples the reductive polyphthalocyanine network and the oxidative metal cluster in a complete framework, and the mutual cooperation between the two promotes rapid electron transfer and effective charge separation, thereby improving the electrocatalytic activity. In summary, as an organic framework material based on metal phthalocyanine, it combines the advantages of rigidity and stable coordination environment, highly conjugated π electron system and easy-to-modify structure. Different functional groups can be modified on the benzene ring structure to form a polyphthalocyanine network with corresponding edge functionalization, and the goal of high active sites can be achieved by designing metal nodes and connectors. It has the potential to be an ideal candidate for oxygen reduction electrocatalytic materials. Summary of the invention

[0005] Based on the above problems existing in the prior art, the present invention provides a method for preparing an organic electrocatalytic material by metal cluster / polyphthalocyanine network composite, wherein the catalytic material improves the catalytic activity of ORR through the synergistic effect of metal clusters and substituent-optimized polyphthalocyanine in a metal-organic framework; and is used in the negative electrode process of batteries such as lithium batteries, fuel cells, sodium batteries and zinc-air batteries.

[0006] 1. Preparation of metal cluster / polyphthalocyanine network composite organic electrocatalytic materials

[0007] The method for preparing metal cluster / polyphthalocyanine network composite organic electrocatalytic material by solvothermal method, the specific preparation process is as follows:

[0008] (1) Preparation of polyphthalocyanine network

[0009] Acid anhydride, chloride salt and urea containing a benzene ring are used as raw materials, which are fully mixed, placed in an oil bath and heated at 150-250° C. for 3-8 hours to perform a solid phase reaction to obtain a black solid; the obtained solid is cooled to room temperature, purified several times with a solvent, filtered and washed clean; the purified solid is dried and cooled to obtain a polyphthalocyanine network precursor;

[0010] (2) Metal cluster / polyphthalocyanine network composite

[0011] The polyphthalocyanine network precursor obtained above is dispersed in a suitable solvent to form solution A; trifluoroacetate and tert-butyl metal compound are mixed in a solvent to form metal clusters, which are dissolved in a suitable solvent to form solution B; the above two solutions are mixed and left overnight, filtered, washed and dried; after the treatment, carbon powder is added for ball milling, solvent is added for dilution to facilitate uniform mixing, and metal cluster / polyphthalocyanine network composite catalytic material is obtained after drying.

[0012] 2. Characterization of Metal Cluster / Polyphthalocyanine Network Composite Organic Electrocatalytic Materials

[0013] Below is M x Taking / p-FePc-X3@C electrocatalytic material as an example, the catalytic material was characterized by XRD and Raman spectroscopy.

[0014] (1) XRD characterization

[0015] In order to obtain more information about catalytic materials, x / p-FePc-X3@C was subjected to XRD test. Figure 1 The test results are shown in Figure 2. It can be seen that there are characteristic peaks of FePc and carbon at around 25 degrees. The XRD test results prove that the components in the catalytic material are in line with expectations.

[0016] (2) Raman spectroscopy characterization

[0017] Figure 2 This is the Raman spectrum characterization result, showing similar A1 g 、B1 g Vibration mode, which is the in-plane vibration of the phthalocyanine-macrocyclic structure. D peak (~1350cm -1 ) and G peak (~1580cm -1 ) is a typical characteristic peak of carbon materials.

[0018] 3. Electrochemical testing of metal cluster / polyphthalocyanine network composite organic electrocatalytic materials

[0019] To illustrate the performance of the prepared metal cluster / polyphthalocyanine network composite organic electrocatalytic material, the following is a x / p-FePc-R@C carbon electrocatalytic material was taken as an example to carry out activity test.

[0020] (1) Catalytic performance test

[0021] In order to regulate the electronic microenvironment of the Fe-N4 center and the corresponding oxygen adsorption stability, such as Figure 3 A model of iron phthalocyanine containing fifteen different electron-withdrawing / donating substituents was systematically constructed, and five representative substituents were selected and named R=R1, R2, R3, R4 and R5. Figure 4 a is M xLSV curves of / p-FePc-R@C samples at a rotation speed of 1600rpm under five different substituent conditions. At a rotation speed of 1600rpm, through the screening of substituents, the catalyst half-wave potentials of the five different substituents are 0.8549V, 0.8713V, 0.9145V, 0.9038V and 0.8679V, respectively. Obviously, it can be seen that M x The half-wave potential of the / p-FePc-R3@C sample is significantly higher than that of the other samples. The substituents are selected based on the gradually increasing electron-withdrawing ability. Figure 4 It can be seen from a that as the electron-withdrawing ability gradually increases, the half-wave potential presents a normal distribution. This is because the introduction of electron-withdrawing substituents can reduce the proportion of electrons in the bonding orbital, have higher electron delocalization and lower energy barriers, promote electron transfer and reduction of oxygen, and thus reduce the binding strength of *OH species. Substituents with too strong electron-withdrawing ability, on the contrary, reduce the catalytic performance. Electron-donating substituents accept more electrons in the σ bonding state, which is not conducive to the desorption of *OH from the Fe-N4 center in the FePc-R model. The best substituent samples were screened with different feed ratios and different carbon powder ratios, and it was found that the best feed ratio was 9:2 and the best carbon powder ratio was 2:4. The highest half-wave potential measured was 0.9658V. The optimal ratio of M x / p-FePc-R3@C is named M x / p-FePc-X3@C.

[0022] Figure 4 b shows the Tafel slope plot made from the LSV curves of the five substituents. The smallest Tafel slope (46.6 mV dec -1 ), which means that M x / p-FePc-R3@C has the highest transfer coefficient for ORR electrocatalytic kinetics.

[0023] Figure 5 M x RRDE curves of / p-FePc-X3@C and Pt / C at 1600rpm. D represents the disk current, I R represents the Faraday current at the electrode ring disk, and the N value represents the collection rate of the disk current: 0.37. Figure 5 As shown in b, the hydrogen peroxide yield is less than 10% (0.4-0.8V), indicating that M x The ORR reaction on p-FePc-X3@C is mainly through the well-established and efficient 4e - Process is underway.

[0024] (2) Comparative sample test

[0025] In order to explore whether the metal clusters have an effect on the catalyst, a control experiment was conducted with and without the addition of metal clusters. Figure 8 . It was found that the E 1 / 2 is 0.8561V, which is higher than M x / p-FePc-X3@C decreased by 0.1097 V. This indicates that using the classic polyphthalocyanine catalyst as a linker to separate the metal clusters spatially and evenly distribute them in the new metal-organic framework can achieve effective charge transfer and electron distribution. By introducing the synergistic effect in the metal-organic framework, the catalytic activity of ORR can be effectively improved.

[0026] (3) Stability test

[0027] Stability is also one of the important parameters to measure catalyst performance. Since long-term electrolysis activities will lead to the decline of catalyst activity, stability is another key factor in evaluating its long-term usability and practical commercial application. x The ORR curves of / p-FePc-X3@C before and after 2500 cycles show ( Figure 6 ), E 1 / 2 The deviation voltage of Pt / C is only 76.9mV. Figure 7 In the chronoamperometric test, the M x / p-FePc-X3@C and Pt / C. It is worth noting that after 45000s, M x The current density of / p-FePc-X3@C remained at 91.09% of the initial value, while that of Pt / C was only 81.58% of the initial value. This indicates that the obtained M x The current retention rate of / p-FePc-X3@C is better than that of Pt / C. Further, by comparing the E 1 / 2 The optimized ratio of carbon black to metal clusters significantly improved the M x The ORR performance and stability of the / p-FePc-X3@C catalyst can be attributed to the strong interaction between carbon black and metal clusters in the hybrid support.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. Compared with platinum-based catalytic materials, the present invention has low cost and simple process, can be mass-produced and supplied in batches. Through the diversified modification of different functional groups, the edge-functionalized polyphthalocyanine network, and the synergistic effect of the polyphthalocyanine network and the metal cluster, the three advantages enable the present invention to achieve a high-efficiency catalytic effect similar to that of platinum-based catalysts in ORR. Therefore, compared with platinum catalytic materials, the present invention significantly reduces the catalyst cost and enhances the service life.

[0030] 2. Compared with other organic catalytic materials, the present invention has better effects and is more stable. The preparation process of the present invention is simple, low-cost, and takes less time. It combines the advantages of organic synthesis, and each step can be precisely controlled by selecting different reaction conditions, catalysts, and reactants, thereby improving the product and yield. In addition, the present invention adopts a polyphthalocyanine network and a metal cluster composite structure, and provides higher conductivity and metal active site density through an in-plane π conjugated structure, so that the material exhibits higher electrocatalytic activity and reaction rate in ORR, enhances the structural stability of the material, and effectively overcomes the poor stability and low catalytic activity of traditional organic catalytic materials.

[0031] 3. Compared with traditional phthalocyanine catalytic materials, the present invention optimizes the polyphthalocyanine network structure and combines phthalocyanine composites with different metal centers (Cu, Co, Zn, Cr, Ni, Fe, Mn), effectively increasing the density of active sites and enhancing the electron transfer capacity. In addition, through the action of the edge blocking agent anhydride, the polyphthalocyanine network obtains a specific edge functionalized structure, which significantly improves the oxygen reduction reaction kinetics of the material. This design not only improves the overall catalytic activity of the material, but also improves the ORR performance under low overpotential, making its reaction efficiency and power density significantly improved compared with traditional phthalocyanine catalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 M x / XRD pattern of p-FePc-X3@C;

[0033] Figure 2 M x Raman spectrum of / p-FePc-X3@C;

[0034] Figure 3 Schematic diagram of the molecular structure of polyphthalocyanine with different substituents;

[0035] Figure 4 (a) is M x LSV curves of / p-FePc-R@C samples with five different substituents;

[0036] Figure 4(b) is a Tafel slope graph made from the LSV curves of five substituents;

[0037] Figure 5 (a) and (b) are M x RRDE curves of / p-FePc-X3@C and Pt / C at 1600rpm;

[0038] Figure 6 This is the ORR accelerated aging curve before and after 2500 cycles;

[0039] Figure 7 This is the chrono current curve for 45000s;

[0040] Figure 8 LSV curves with and without metal clusters added. DETAILED DESCRIPTION

[0041] The preparation and performance of the metal cluster / polyphthalocyanine network composite organic oxygen reduction electrocatalytic material of the present invention are further described below through specific examples.

[0042] Example 1

[0043] Preparation and ORR performance of Ni / p-FePc-X@C catalyst

[0044] (1) Preparation of polyphthalocyanine network precursor: First, 4.0 g of ammonium chloride, 4.0 g of anhydride containing a benzene ring and 0.28 g of ferrous chloride were mixed, placed in an oil bath and heated at 240°C for 5 h to obtain a black solid. The obtained solid was cooled to room temperature, purified several times with a solvent, filtered and washed. Dry at 70°C for 20 h, and after drying, cooled to obtain a polyphthalocyanine network precursor.

[0045] (2) Preparation of metal cluster / polyphthalocyanine network composite catalytic materials

[0046] The polyphthalocyanine network precursor obtained above is dispersed in a suitable solvent to form solution A; nickel trifluoroacetate and tert-butyl nickel are mixed in a solvent to form a metal cluster, which is dissolved in a suitable solvent to form solution B; the above two solutions are mixed and left overnight, filtered, washed and dried; after the treatment, carbon powder is added for ball milling, a solvent is added for dilution to facilitate uniform mixing, and a metal cluster / polyphthalocyanine network composite catalytic material is obtained after drying.

[0047] (3) ORR performance of metal cluster / polyphthalocyanine network composite catalyst: For the prepared metal cluster / polyphthalocyanine network composite catalyst, LSV test was carried out, and the half-wave potential was 0.8149 V, 0.8623 V, 0.9041 V, 0.8938 V and 0.8609 V, respectively. It remained stable for 20 hours and had good catalytic performance.

[0048] Example 2

[0049] Preparation and ORR performance of Cu / p-CoPc-X3@C catalyst

[0050] (1) Preparation of polyphthalocyanine network precursor: First, 4.0 g of ammonium chloride, 4.0 g of anhydride containing a benzene ring and 0.28 g of cobalt chloride were mixed, placed in an oil bath and heated at 240°C for 5 h to obtain a black solid. The obtained solid was cooled to room temperature, purified several times with a solvent, filtered and washed. Dry at 70°C for 20 h, and after drying, cooled to obtain a polyphthalocyanine network precursor.

[0051] (2) Preparation of metal cluster / polyphthalocyanine network composite catalytic materials

[0052] The polyphthalocyanine network precursor obtained above is dispersed in a suitable solvent to form solution A; copper trifluoroacetate and tert-butyl copper are mixed in a solvent to form a metal cluster, which is dissolved in a suitable solvent to form solution B; the above two solutions are mixed and left overnight, filtered, washed and dried; after the treatment, carbon powder is added for ball milling, a solvent is added for dilution to facilitate uniform mixing, and a metal cluster / polyphthalocyanine network composite catalytic material is obtained after drying.

[0053] (3) ORR performance of metal cluster / polyphthalocyanine network composite catalyst: For the prepared metal cluster / polyphthalocyanine network composite catalyst, LSV test was carried out, and the half-wave potential was 0.8129 V, 0.8323 V, 0.9001 V, 0.8838 V and 0.8605 V, respectively. It remained stable for 20 hours and had good catalytic performance.

[0054] Example 3

[0055] Preparation and ORR performance of Zn / p-CoPc-X@C catalyst

[0056] (1) Preparation of polyphthalocyanine network precursor: First, 4.0 g of ammonium chloride, 4.0 g of anhydride containing a benzene ring and 0.28 g of cobalt chloride were mixed, placed in an oil bath and heated at 240°C for 5 h to obtain a black solid. The obtained solid was cooled to room temperature, purified several times with a solvent, filtered and washed. Dry at 70°C for 20 h, and after drying, cooled to obtain a polyphthalocyanine network precursor.

[0057] (2) Preparation of metal cluster / polyphthalocyanine network composite catalytic materials

[0058] The polyphthalocyanine network precursor obtained above is dispersed in a suitable solvent to form solution A; zinc trifluoroacetate and tert-butyl zinc are mixed in a solvent to form a metal cluster, which is dissolved in a suitable solvent to form solution B; the above two solutions are mixed and left overnight, filtered, washed and dried; after the treatment, carbon powder is added for ball milling, a solvent is added for dilution to facilitate uniform mixing, and a metal cluster / polyphthalocyanine network composite catalytic material is obtained after drying.

[0059] (3) ORR performance of metal cluster / polyphthalocyanine network composite catalyst: For the prepared metal cluster / polyphthalocyanine network composite catalyst, LSV test was carried out, and the half-wave potential was 0.8123V, 0.8353V, 0.8605V, 0.8838V and 0.9021V, respectively. It remained stable for 20 hours and had good catalytic performance.

[0060] Comparative Example 1

[0061] Preparation and ORR Performance of Ni / p-FePc-X Catalyst

[0062] (1) Preparation of polyphthalocyanine network precursor: First, 4.0 g of ammonium chloride, 4.0 g of anhydride containing a benzene ring and 0.28 g of ferrous chloride were mixed, placed in an oil bath and heated at 240°C for 5 h to obtain a black solid. The obtained solid was cooled to room temperature, purified several times with a solvent, filtered and washed. Dry at 70°C for 20 h, and after drying, cooled to obtain a polyphthalocyanine network precursor.

[0063] (2) Preparation of polyphthalocyanine network catalytic materials

[0064] The polyphthalocyanine network precursor obtained above is added with carbon powder for ball milling, and a solvent is added for dilution to facilitate uniform mixing, and the polyphthalocyanine network catalytic material is obtained after drying.

[0065] (3) ORR performance of polyphthalocyanine network catalytic material catalyst: For the prepared polyphthalocyanine network catalyst, such as Figure 8 The LSV test showed that the half-wave potentials were 0.7149 V, 0.7623 V, 0.8561 V, 0.7948 V, and 0.7609 V, respectively. The stability was maintained for 15 hours, and the catalytic performance was poor. This was because no metal clusters were added, and no synergy was introduced into the metal-organic framework, which made it impossible to achieve effective charge transfer and electron distribution, and ultimately led to poor catalytic activity for ORR.

Claims

1. A method for using a metal cluster / polyphthalocyanine network composite organic oxygen reduction electrocatalytic material, comprising the following steps: (1) Preparation of polyphthalocyanine network precursor Acid anhydride, chloride salt and urea containing a benzene ring are used as raw materials, which are fully mixed, placed in an oil bath and heated for a certain period of time for solid phase reaction to obtain a black solid; the obtained solid is cooled to room temperature, purified several times with a solvent, filtered and washed clean; the purified solid is dried and cooled to obtain a polyphthalocyanine network precursor; (2) Preparation of metal cluster / polyphthalocyanine network composite catalytic materials The polyphthalocyanine network precursor obtained above is dispersed in a suitable solvent to form solution A; trifluoroacetate and tert-butyl metal compound are mixed in a solvent to form metal clusters, which are dissolved in a suitable solvent to form solution B; the above two solutions are mixed and left overnight, filtered, washed and dried; after the treatment, carbon powder is added for ball milling, solvent is added for dilution to facilitate uniform mixing, and metal cluster / polyphthalocyanine network composite catalytic material is obtained after drying.

2. The method for preparing a metal cluster / polyphthalocyanine network composite organic electrocatalytic material according to claim 1, characterized in that: In step (1), the acid anhydride containing a benzene ring, a chloride salt and urea are used as raw materials in a mass ratio of 1:1:1 to 1:100:

200.

3. The method for preparing a metal cluster / polyphthalocyanine network composite organic electrocatalytic material according to claim 1, characterized in that: In step (1), the heating temperature in the oil bath is 150-250° C. and the heating time is 3-8 h.

4. The method for preparing a metal cluster / polyphthalocyanine network composite organic electrocatalytic material according to claim 1, characterized in that: In step (1), the chloride salt may be one or more of KCl, CuCl2, CoCl2, ZnCl2, NH4Cl, AgCl, NiCl2, FeCl2, FeCl3 and MnCl2.

5. The method for preparing a metal cluster / polyphthalocyanine network composite organic electrocatalytic material according to claim 1, characterized in that: In steps (1) and (2), the solvent is one or more of ultrapure water, acetone, methanol, ethanol, propanol, dichloromethane, ethyl acetate and tetrahydrofuran.

6. The method for preparing a metal cluster / polyphthalocyanine network composite organic electrocatalytic material according to claim 1, characterized in that: In step (2), the mixing ratio of solution A to solution B is 1:1 to 1:300, and the mass ratio of the polyphthalocyanine network precursor to the metal cluster is 1:1 to 1:

200.

7. The method for preparing a metal cluster / polyphthalocyanine network composite organic electrocatalytic material according to claim 1, characterized in that: In step (2), the metal cluster is one or more of a silver cluster, a copper cluster, a nickel cluster, a zinc cluster and a palladium cluster.

8. The method for preparing a metal cluster / polyphthalocyanine network composite organic electrocatalytic material according to claim 1, characterized in that: In step (2), the size of the metal cluster is 1 to 500 nm.

9. The method for preparing a metal cluster / polyphthalocyanine network composite organic electrocatalytic material according to claim 1, characterized in that: In step (2), the metal cluster is prepared from trifluoroacetate and a tert-butyl metal compound, and the metal ion can be Cu 2+ 、Co 2+ 、Zn 2+ Cr 3+ 、Ag + 、Ni 2+ , Fe 2+ and Mn 2+ .

10. Use of the metal cluster / polyphthalocyanine network composite organic electrocatalytic material prepared by the method according to claim 1 in cathode oxygen reduction of devices such as lithium batteries, sodium batteries, and fuel cells.

Citation Information

Cited By

  • Fe-N-C bifunctional catalyst with enhanced pi conjugation effect as well as preparation method and application of Fe-N-C bifunctional catalyst

    CN120511313A

  • Conjugated organic polymer electrocatalyst as well as preparation method and application thereof

    CN121839720A